Levels of selection in evolution - Keller, Laurent, 1961- (Monographs in behavior and ecology., 1999)
Evolutionary biologists have recognised that natural selection operates for the good of lower-level units (the individual, the cell, even the gene) rather than the good of the group. In this volume, 12 scientists discuss why this should be the case.